Securing a sustainable future: A path towards gender equality in the Indian agricultural sector - Dharamshi, Khyati; Moskovitz, Liora; Munshi, Sugandha (MDPI, 2023)
The Indian agricultural sector is the world’s largest producer of pulses, milk, and jute, and the second-largest producer of rice, wheat, vegetables, fruit, and cotton. Climate change threatens food security worldwide and has severely impacted the Indian agricultural sector. As a result of the unpredictable climate and low profits, economic uncertainty has forced men to seek employment in non-farming sectors. Under the deepening crisis, the farming landscape has transformed into a female-majority workforce. To identify pragmatic solutions to the deepening agrarian crisis, we employed a qualitative triangulation approach to our investigation of the feminisation of the farming sector, which was conducted in 2020. Our analyses of Indian media narratives, archive stories, responses to an online story completion task, and in-depth expert interviews show that, despite their developing role and increasing contribution, women remain marginalised and discriminated against in a culturally male-dominant sector. Supported by a long-term field ethnographic experience, we used Installation Theory to identify three domains in which policymakers can intervene to promote the interconnected issues of social sustainability, gender equality, and sustainable economic development in this sector.